Evaluation of serum ferritin as a marker for adult Still's disease activity. Issue 5 (May 1992) - Schwarz-Eywill, M; Heilig, B; Bauer, H; Breitbart, A; Pezzutto, A
Abstract : Extremely high serum ferritin values (greater than 10, 000 micrograms/l) were detected in two patients with adult Still's disease. The ferritin concentrations decreased to normal after adequate treatment. During a one year follow up ferritin concentration was helpful in monitoring disease activity and guiding decisions about treatment. Raised concentrations of soluble interleukin 2 receptors (sCD25) were also found. Detection of ferritin values above 3000 micrograms/l should lead to the consideration of Still's disease when there is an acute febrile illness without evidence for bacterial or viral infections, serum ferritin being suitable for monitoring treatment.